Pengembangan Rencana Pelaksanaan Pembelajaran Menggunakan Model Pembelajaran Inkuiri pada Pembelajaran Tematik Kelas IV SDN Kota Bengkulu - Shinta Setiana; Nani Yuliantini (JURIDIKDAS, 2023)
This study aims to develop a learning implementation plan using inquiry learning models in Thematic learning in class IV Bengkulu City. This type of research is research and development. This study uses a 4D development model by Thiagarajan. However, this research was only carried out up to the 3D stage (Define, Design, Develop). Validation is done by design experts and material experts. The lesson plan (RPP) developed was rated and responded by 2 teachers from Bengkulu City Elementary School. Data analysis techniques used descriptive statistical analysis of the results of the expert validation research and teacher responses and qualitative descriptive analysis of the comments from the expert validation and teacher responses. The score of the validator assessment of the lesson plan (RPP) with a score of 86.92 with a very valid category and the teacher's response of 91 with a very good category.